Pengaruh Gaya Kepemimpinan Trasformasional, Iklim Sekolah, Motivasi Kerja, Etos Kerja Terhadap Komitmen Organisasional Guru di Sekolah Dasar Gugus R.A. Kartini Kota Denpasar Tahun 2022 - I Nyoman Werna; I Putu Wisna Ariawan; I Made Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to obtain certainty of simultaneous data on the magnitude of the influence of the principal's leadership style, work climate, work motivation, and teacher work ethic, on the organizational commitment of elementary school teachers at Guus RA Kartini in Denpasar City. This type of research is